Exploring the mediating processes of quality of governance between foreign direct investment and economic growth / Fazlida Mohd Razali ... [et al.] - Mohd Razali, Fazlida; Md Zin, Norlaila; Mohd Padil, Hazlina; Kasim, Eley Suzana (UiTM Cawangan Negeri Sembilan, 2023)
Foreign direct investment contributes to the changes in economic growth of ASEAN countries. Past studies showed mixed nature of relationship between foreign direct investment and economic growth. Good governance factors such as government effectiveness, political stability and absence of violence, rule of law, voice and accountability, control of corruption and regulatory quality also showed positive significant effect on economic growth. However, there is a lack of evidence on the mediating process of quality of governance between foreign direct investment and economic growth. Hence, this study aims to explain the process of quality of governance in mediating the relationship between FDI and economic growth. This study analysed secondary data for the period from 2009 to 2020 of five ASEAN countries with high human development scores based on the 2020 Human Development Report by the United Nations. Findings indicated that quality of governance mediates and improves the relationship between foreign direct investment and economic growth. The findings have significant policy implications as they suggest that policymakers in ASEAN countries can foster economic growth by further promoting FDI whilst considering the appropriate governance mechanism that can enhance economic growth.